Business case as essential element of the implementation LPV GNSS procedures - Andrzej FELLNER; Henryk JAFERNIK (Scientific Journal of Silesian University of Technology. Series Transport)
The purpose of this document is to develop a Business Case for implementing a new RNAV approach to LNAV and LPV minima for the Mielec aerodrome (EPML). This business case aims to assist the management of small airports such as MIELEC, in their decision to implement RNAV procedures, by providing as much as possible relevant information. The basic methodology can be therefore reused in similar airports as long as the assumptions made for each case are updated. The document is a deliverable of the TEN-T funded programme “Support to the EGNOS APV Operational Implementation – APV MIELEC.